Changes in performance practice since the 1970s as exemplified in selected recordings of JS Bach's English Suite No 4 in F Major (BWV 809) - Van Wyk, W. (University of Pretoria, 2016)
Mini Dissertation (MMus)--University of Pretoria, 2015.